The Issue of Relationship in Lotman's Writing and the Russian Language Today - Verbitskaya L.A (Moscow State University of Psychology and Education, 2015)
The article is devoted to the memory of Y.M. Lotman, who attended lectures at the Faculty of Philology of the St. Petersburg (Leningrad) University as schoolboy, was a student of philology during the so-called "Leningrad Affair" (1946-1950). The article highlights the link between communication, mutual understanding, and the Russian language nowadays. The author notes the changes that have occurred over the past two decades in the style and vocabulary of the Russian language and points to the deep connection between language, culture and understanding in society. The article gives an examples of improper borrowing and vulgarization of the modern Russian language and argued that a reasonable literary language policy is a struggle not only and not so much for its purity, but for the preservation of national cultural heritage and identity of the nation. Preservation of the language is definitely an issue of the country security.